Nonaqueous electrolyte power storage element and method for manufacturing the same

The non-aqueous electrolyte storage device with a lithium alloy negative electrode and high unsaturated cyclic carbonate content addresses the low discharge capacity issue in Li-S batteries by suppressing lithium ion overvoltage and forming a protective film, resulting in enhanced discharge performance.

JP2025009016APending Publication Date: 2025-01-20GS YUASA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023111718
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-06
Publication Date
2025-01-20

Smart Images

  • Figure 2025009016000001_ABST
    Figure 2025009016000001_ABST
Patent Text Reader

Abstract

To provide a nonaqueous electrolyte power storage element that includes a positive electrode containing a sulfur element and has a large ratio of a charge capacity in first charge relative to a discharge capacity in first discharge and a large discharge capacity in second discharge.SOLUTION: A nonaqueous electrolyte power storage element includes: a positive electrode containing a sulfur element; a negative electrode having a lithium alloy; and a nonaqueous electrolyte containing an unsaturated cyclic carbonate. The lithium alloy contains at least one of an aluminum element, an indium element, a zinc element, and a calcium element. Content of the unsaturated cyclic carbonate in the whole nonaqueous solvent of the nonaqueous electrolyte is more than 50 vol% and 100 vol% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a nonaqueous electrolyte electricity storage element and a method for producing a nonaqueous electrolyte electricity storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] Known non-aqueous electrolyte storage elements include Li-S batteries and other non-aqueous electrolyte storage elements that use a positive electrode containing elemental sulfur. Patent Document 1 describes a lithium-sulfur battery (Li-S battery) that has a positive electrode active material containing a sulfur-based material and a negative electrode active material containing lithium metal. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2002-75447 A Summary of the Invention [Problem to be solved by the invention]

[0005] Li-S batteries are expected to be a storage element with high energy density because of the large theoretical capacity of sulfur. However, the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge is small, and as a result, the discharge capacity at the second discharge is also small.

[0006] The present invention has been made in light of the above circumstances, and has an object to provide a nonaqueous electrolyte storage element including a positive electrode containing elemental sulfur, which has a large ratio of charge capacity at the first charge to discharge capacity at the first discharge, and a large discharge capacity at the second discharge. [Means for solving the problem]

[0007] A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode containing elemental sulfur, a negative electrode having a lithium alloy, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, wherein the lithium alloy contains at least one of elemental aluminum, elemental indium, elemental zinc, and elemental calcium, and the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50% by volume and not more than 100% by volume.

[0008] A method for manufacturing a nonaqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode containing elemental sulfur, preparing a negative electrode having a lithium alloy, and preparing a nonaqueous electrolyte containing an unsaturated cyclic carbonate, wherein the lithium alloy contains at least one of elemental aluminum, elemental indium, elemental zinc, and elemental calcium, and the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50% by volume and not more than 100% by volume. Effect of the Invention

[0009] According to one aspect of the present invention, it is possible to provide a nonaqueous electrolyte storage element including a positive electrode containing elemental sulfur, in which the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and the discharge capacity at the second discharge are large. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] First, an outline of the nonaqueous electrolyte storage element and the method for producing the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0012] (1) A nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode containing elemental sulfur, a negative electrode having a lithium alloy, and a nonaqueous electrolyte containing an unsaturated cyclic carbonate, wherein the lithium alloy contains at least one of elemental aluminum, elemental indium, elemental zinc, and elemental calcium, and the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50% by volume and not more than 100% by volume.

[0013] The nonaqueous electrolyte storage element described in (1) above is a nonaqueous electrolyte storage element having a positive electrode containing elemental sulfur, and has a high ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and a high discharge capacity at the second discharge. Although the reason for this is unclear, the following reason is presumed. The nonaqueous electrolyte storage element described in (1) above includes a positive electrode containing a sulfur element and a negative electrode having a lithium alloy. In the conventional nonaqueous electrolyte storage element, the overvoltage for reducing (precipitating) lithium ions in the negative electrode after the first discharge is large, and therefore the initial charge capacity is small. In contrast, the lithium alloy in the negative electrode of the nonaqueous electrolyte storage element described in (1) above contains at least one of aluminum, indium, zinc, and calcium elements, thereby improving the electrical conductivity, and thus suppressing the overvoltage for precipitating lithium ions in the negative electrode (hereinafter also referred to as "precipitating overvoltage"). In addition, the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte of the nonaqueous electrolyte storage element described in (1) above is within the above range, and thus a good coating derived from the unsaturated cyclic carbonate is formed on the surface of the negative electrode. This suppresses contact between the negative electrode surface and the nonaqueous electrolyte after the coating is formed, and the thickness of the coating is unlikely to increase, thereby suppressing an increase in the deposition overvoltage of lithium ions on the surface of the negative electrode. Therefore, the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge is large. Also, because this ratio is large, the discharge capacity at the second discharge is also large.

[0014] The "positive electrode containing elemental sulfur" means, for example, that when the positive electrode has a positive electrode active material layer containing a positive electrode active material, the positive electrode active material layer may contain elemental sulfur, or the positive electrode active material may contain elemental sulfur.

[0015] The "content of unsaturated cyclic carbonate in all non-aqueous solvents" is obtained by converting the mass of each non-aqueous solvent measured by gas chromatography mass spectrometry (GC-MS analysis) in accordance with JIS-K-0123 (2018) into its volume at 25°C and 1 atmosphere.

[0016] The content of the unsaturated cyclic carbonate in the total nonaqueous solvent is not the content of the unsaturated cyclic carbonate in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte storage element, but the content of the unsaturated cyclic carbonate in the nonaqueous electrolyte provided in the completed nonaqueous electrolyte storage element. Usually, the nonaqueous electrolyte storage element is completed by assembling a non-charged / discharged nonaqueous electrolyte storage element and then performing an initial discharge and an initial charge (hereinafter also referred to as "initial charge / discharge"). During the initial charge / discharge, a part of the unsaturated cyclic carbonate is consumed for the formation of a coating on the negative electrode surface, etc. For this reason, it is considered that the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte provided in the completed nonaqueous electrolyte storage element is reduced compared to the content of the unsaturated cyclic carbonate in the nonaqueous electrolyte used in the manufacture of the nonaqueous electrolyte storage element. The initial charge and discharge may be performed after assembling a non-charged and discharged non-aqueous electrolyte storage element, for example, to check the capacity or to activate a specific positive electrode active material, and refers to the charge and discharge performed before the non-aqueous electrolyte storage element is shipped or used as a completed product. However, there is a certain degree of correlation between the content of the unsaturated cyclic carbonate in the non-aqueous electrolyte used in the manufacture of the non-aqueous electrolyte storage element and the content of the unsaturated cyclic carbonate remaining in the non-aqueous electrolyte of the completed non-aqueous electrolyte storage element. Therefore, if the content of the unsaturated cyclic carbonate remaining in the non-aqueous electrolyte of the completed non-aqueous electrolyte storage element is within the above range, it can be said that the non-aqueous electrolyte used in the manufacture of the non-aqueous electrolyte storage element contains a sufficient amount of the unsaturated cyclic carbonate to form a good coating derived from the unsaturated cyclic carbonate on the negative electrode surface during initial charge and discharge. In this case, a non-aqueous electrolyte storage element can be provided that has a high ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and a high discharge capacity at the second discharge.

[0017] (2) In the nonaqueous electrolyte storage element described in (1) above, the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte may be 70% by volume or more.

[0018] In the nonaqueous electrolyte storage element described in (2) above, since the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is equal to or greater than the lower limit, a good coating derived from the unsaturated cyclic carbonate is more reliably formed on the negative electrode surface, and therefore the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and the discharge capacity at the second discharge are larger.

[0019] (3) In the nonaqueous electrolyte storage element according to (1) or (2) above, the lithium alloy may contain aluminum or indium, and the content of aluminum or indium in the lithium alloy may be 5% by mass or more and 20% by mass or less.

[0020] In the nonaqueous electrolyte storage element described in (3) above, the lithium alloy has an aluminum element or indium element content within the above range, so that the precipitation overvoltage of lithium ions in the negative electrode is further suppressed, and therefore the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and the discharge capacity at the second discharge are larger.

[0021] The content of each metal element in the lithium alloy contained in the negative electrode is measured by ICP emission spectrometry in accordance with JIS-K-0116 (2014).

[0022] The sample to be measured in the above-mentioned ICP atomic emission spectrometry is collected in the following manner. First, the nonaqueous electrolyte storage element after the initial charge and discharge is charged at a constant current of 0.1C to the charge end voltage during normal use, and is fully charged. Here, normal use refers to the case where the nonaqueous electrolyte storage element is used by adopting the charge and discharge conditions recommended or specified for the nonaqueous electrolyte storage element. Next, the nonaqueous electrolyte storage element in the fully charged state is disassembled, and the positive electrode and the negative electrode are taken out. In addition, the positive electrode and the negative electrode are thoroughly washed with dimethyl carbonate to remove the attached components (nonaqueous electrolyte, etc.), and then dried under reduced pressure at room temperature for 24 hours. Then, the lithium alloy is taken from the negative electrode and used as a sample to be measured for ICP atomic emission spectrometry. In addition, in order to measure the content of lithium element derived from the lithium alloy of the negative electrode that was inserted into the positive electrode and remained after being dissolved from the negative electrode in the nonaqueous electrolyte by the above initial charge and discharge, the positive electrode active material layer taken from the positive electrode is also used as a sample to be measured for ICP atomic emission spectrometry. The content of each metal element in the lithium alloy is the sum of the content of each metal element contained in the lithium alloy extracted from the negative electrode by the above method and the content of lithium element contained in the positive electrode active material layer extracted from the positive electrode. Note that the process from disassembly of the nonaqueous electrolyte storage element to the collection of the measurement sample is carried out in an argon atmosphere with a dew point of -60°C or lower.

[0023] (4) In the nonaqueous electrolyte storage element according to (1) or (2) above, the lithium alloy may contain zinc or calcium, and the content of zinc or calcium in the lithium alloy may be 1% by mass or more and 10% by mass or less.

[0024] In the nonaqueous electrolyte storage element described in (4) above, the content of zinc element or calcium element in the lithium alloy is within the above range, so that the precipitation overvoltage of lithium ions in the negative electrode is further suppressed, and therefore the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and the discharge capacity at the second discharge are larger.

[0025] (5) A method for producing a nonaqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode containing elemental sulfur, preparing a negative electrode having a lithium alloy, and preparing a nonaqueous electrolyte containing an unsaturated cyclic carbonate, wherein the lithium alloy contains at least one of elemental aluminum, elemental indium, elemental zinc, and elemental calcium, and the content of the unsaturated cyclic carbonate in a total nonaqueous solvent of the nonaqueous electrolyte is more than 50% by volume and not more than 100% by volume.

[0026] The method for producing a nonaqueous electrolyte storage element described in (5) above uses a negative electrode having a lithium alloy containing at least one of aluminum, indium, zinc, and calcium, and therefore can provide a nonaqueous electrolyte storage element in which the deposition overvoltage of lithium ions at the negative electrode is suppressed. In addition, a nonaqueous electrolyte in which the content of unsaturated cyclic carbonate in the total nonaqueous solvent is within the above range is used, and therefore a good coating derived from the unsaturated cyclic carbonate is formed on the surface of the negative electrode. Therefore, the method for producing a nonaqueous electrolyte storage element described in (5) above can provide a nonaqueous electrolyte storage element in which the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge and the discharge capacity at the second discharge are large.

[0027] Hereinafter, a nonaqueous electrolyte electricity storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte electricity storage element according to one embodiment of the present invention, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0028] [Non-aqueous electrolyte energy storage element] A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually of a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator interposed therebetween, or of a wound type in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state that it is contained in the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.

[0029] <Positive electrode> The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. In one embodiment of the present invention, the positive electrode contains elemental sulfur as a positive electrode active material, which will be described later.

[0030] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2 The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0031] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0032] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0033] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, if necessary, any optional components such as a conductive agent, a binder, a thickener, and a filler.

[0034] The positive electrode active material layer contains sulfur element as a positive electrode active material. The sulfur element as the positive electrode active material may be simple sulfur or a sulfur compound. Examples of the sulfur compound include metal sulfides such as lithium sulfide, organic disulfide compounds, and organic sulfur compounds such as carbon sulfide compounds. The positive electrode active material containing sulfur element has the advantages of high theoretical capacity and low cost.

[0035] The sulfur element may be in the form of a complex with a conductive agent (a material having higher conductivity than simple sulfur or a sulfur compound). The complex may be in the form in which simple sulfur or a sulfur compound is supported on a conductive agent as a carrier, and specifically, may be a complex of simple sulfur or a sulfur compound and porous carbon (sulfur-porous carbon composite: SPC). The lower limit of the content of the sulfur element in this SPC is preferably 50 mass%, more preferably 60 mass%. Meanwhile, the upper limit of the content is preferably 90 mass%, more preferably 80 mass%. By setting the content of the sulfur element in the SPC to the above range, it is possible to achieve both large electric capacity and good conductivity.

[0036] The lower limit of the content of the sulfur element in the positive electrode active material layer is preferably 40% by mass, more preferably 50% by mass. Meanwhile, the upper limit of this content is preferably 90% by mass, more preferably 70% by mass. When SPC is used, the lower limit of the content of SPC in the positive electrode active material layer is preferably 60% by mass, more preferably 80% by mass. Meanwhile, the upper limit of this content is preferably 95% by mass, more preferably 90% by mass. By setting the content of the sulfur element or SPC within the above range, it is possible to achieve both high electric capacity and good conductivity, and to increase the energy density, etc.

[0037] The positive electrode active material may contain other positive electrode active materials in addition to elemental sulfur, but the lower limit of the content of elemental sulfur or SPC in the entire positive electrode active material is preferably 50 mass%, more preferably 90 mass%, and even more preferably 99 mass%.

[0038] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0039] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferred from the viewpoint of electronic conductivity and coatability, and acetylene black is preferred among them. The conductive agent may be in the form of a complex with the above-mentioned sulfur element, or in a form other than the complex with the sulfur element. That is, for example, the positive electrode active material layer may contain a conductive agent that constitutes the SPC and other conductive agents other than the conductive agent.

[0040] The content of the conductive agent (excluding the above-mentioned complex with sulfur element) in the positive electrode active material layer is preferably 1 mass% or more and 15 mass% or less, more preferably 1.5 mass% or more and 10 mass% or less. By setting the content of the conductive agent in the above range, the energy density of the nonaqueous electrolyte storage element can be increased.

[0041] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic acid, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0042] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.

[0043] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium or the like, the functional group may be deactivated in advance by methylation or the like. In one embodiment of the present invention, it may be preferable that the thickener is not contained in the positive electrode active material layer.

[0044] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, and their artificial products. In one embodiment of the present invention, it may be preferable that the filler is not contained in the positive electrode active material layer.

[0045] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0046] <Negative electrode> The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode. In one embodiment of the present invention, the negative electrode has a lithium alloy as the negative electrode active material described later.

[0047] The negative electrode substrate has electrical conductivity. The material of the negative electrode substrate may be copper, nickel, stainless steel, nickel-plated steel, carbonaceous material, or the like. Among these, nickel or nickel alloy is preferred. The negative electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, or the like, and from the viewpoint of cost, a foil is preferred. Therefore, the negative electrode substrate is preferably a nickel foil or a nickel alloy foil. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0048] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0049] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0050] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0051] The negative electrode active material layer contains a lithium alloy as a negative electrode active material. The lithium alloy contains at least one of aluminum (Al), indium (In), zinc (Zn) and calcium (Ca). That is, the lithium alloy contains lithium and one or more selected from the group consisting of aluminum, indium, zinc and calcium. The lithium alloy is, for example, a solid solution of lithium and at least one of aluminum, indium, zinc and calcium.

[0052] The lithium alloy is preferably composed of lithium element (Li) and at least one of aluminum (Al), indium (In), zinc (Zn) and calcium (Ca). In this case, the lithium alloy may contain typical elements and transition metal elements other than the above elements as inevitable impurities, but is preferably composed substantially of lithium element (Li) and at least one of aluminum (Al), indium (In), zinc (Zn) and calcium (Ca). Here, "substantially" means that the content of inevitable impurities is 1 mass% or less.

[0053] Examples of the lithium alloy include Li-Al alloy, Li-In alloy, Li-Al-In alloy, Li-Zn alloy, Li-Ca alloy, and Li-Zn-Ca alloy. Among these, Li-Al alloy, Li-In alloy, Li-Zn alloy, and Li-Ca alloy are preferred.

[0054] The lower limit of the total content of aluminum, indium, zinc and calcium elements in the lithium alloy is preferably 1 mass%, more preferably 2 mass%, and even more preferably 5 mass%. On the other hand, the upper limit of the total content in the lithium alloy is preferably 25 mass%, more preferably 22 mass%, and even more preferably 20 mass%. When the total content in the lithium alloy is equal to or greater than the lower limit, the deposition overvoltage of lithium ions in the negative electrode is easily suppressed. In addition, when the total content in the lithium alloy is equal to or less than the upper limit, the lithium alloy can be easily produced. The total content in the lithium alloy can be equal to or greater than any of the lower limits and equal to or less than any of the upper limits.

[0055] When the lithium alloy contains aluminum or indium, the lower limit of the content of aluminum or indium in the lithium alloy is preferably 5% by mass, more preferably 8% by mass, and even more preferably 10% by mass. On the other hand, the upper limit of the content of aluminum or indium in the lithium alloy is preferably 25% by mass, more preferably 22% by mass, and even more preferably 20% by mass. When the content of aluminum or indium in the lithium alloy is equal to or more than the lower limit, the deposition overvoltage of lithium ions in the negative electrode is easily suppressed. In addition, when the content of aluminum or indium in the lithium alloy is equal to or less than the upper limit, the lithium alloy can be easily produced. The content of aluminum or indium in the lithium alloy can be equal to or more than any of the lower limits and equal to or less than any of the upper limits. In addition, when the lithium alloy contains both aluminum and indium, the total content of aluminum and indium in the lithium alloy can be equal to or more than any of the lower limits and equal to or less than any of the upper limits of the content of aluminum or indium in the lithium alloy.

[0056] When the lithium alloy contains zinc or calcium, the lower limit of the content of zinc or calcium in the lithium alloy is preferably 1% by mass, more preferably 2% by mass, and even more preferably 5% by mass. On the other hand, the upper limit of the content of zinc or calcium in the lithium alloy is preferably 15% by mass, more preferably 12% by mass, and even more preferably 10% by mass. When the content of zinc or calcium in the lithium alloy is equal to or more than the lower limit, the deposition overvoltage of lithium ions in the negative electrode is easily suppressed. In addition, when the content of zinc or calcium in the lithium alloy is equal to or less than the upper limit, the lithium alloy can be easily produced. The content of zinc or calcium in the lithium alloy can be equal to or more than any of the lower limits and equal to or less than any of the upper limits. In addition, when the lithium alloy contains both zinc and calcium, the total content of zinc and calcium in the lithium alloy can be equal to or more than any of the lower limits and equal to or less than any of the upper limits of the content of zinc or calcium in the lithium alloy.

[0057] The negative electrode active material may contain other negative electrode active materials than the lithium alloy, but the content of the lithium alloy in the total negative electrode active material is preferably 50% by mass or more and 100% by mass or less, more preferably 90% by mass or more and 100% by mass or less, and even more preferably 99% by mass or more and 100% by mass or less.

[0058] The negative electrode active material other than the lithium alloy can be appropriately selected from known negative electrode active materials. Examples of the negative electrode active material other than the lithium alloy include metals or semi-metals such as Si and Sn; metal oxides or semi-metal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0059] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0060] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0061] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as the negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.

[0062] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0063] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0064] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass or more and 100% by mass or less, and more preferably 90% by mass or more and 100% by mass or less. By setting the content of the negative electrode active material in the above range, it is possible to achieve both high energy density and manufacturability of the negative electrode active material layer. When the negative electrode active material is composed of only a lithium alloy, the content of the negative electrode active material in the negative electrode active material layer may be 99% by mass or more, or may be 100% by mass.

[0065] The negative electrode active material layer may be a non-porous layer (solid layer) or a porous layer, but is preferably a non-porous layer. The negative electrode active material layer may be a lithium alloy layer. The average thickness of the negative electrode active material layer is preferably 5 μm to 1,000 μm, more preferably 10 μm to 500 μm, and even more preferably 30 μm to 300 μm.

[0066] <separator> The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0067] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.

[0068] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0069] As the separator, a polymer gel composed of a polymer and an electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0070] <Non-aqueous electrolyte> The non-aqueous electrolyte may be a non-aqueous electrolytic solution that contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent.

[0071] The non-aqueous solvent contains an unsaturated cyclic carbonate. The unsaturated cyclic carbonate may be a cyclic carbonate containing an unsaturated bond in the ring structure, or may be a cyclic carbonate containing a carbon-carbon double bond in the ring structure. The number of ring members in the ring structure of the unsaturated cyclic carbonate is preferably 3 to 8, more preferably 4 to 6, and even more preferably 5. In addition, the unsaturated cyclic carbonate may be one in which some of the hydrogen atoms are substituted with halogen, but it is preferable that the hydrogen atoms are not substituted with halogen. In this way, the non-aqueous solvent contains an unsaturated cyclic carbonate, and thus a good coating derived from this unsaturated cyclic carbonate can be formed on the negative electrode surface.

[0072] Examples of the unsaturated cyclic carbonate include vinylene carbonate (VC), methylvinylene carbonate, ethylvinylene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, vinylethylene carbonate (VEC), styrene carbonate, etc. Among these, VC is preferred.

[0073] The non-aqueous solvent may contain other non-aqueous solvents other than the unsaturated cyclic carbonate. Examples of other non-aqueous solvents include saturated cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As other non-aqueous solvents, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used. Among these, from the viewpoint of improving the capacity maintenance rate in the charge-discharge cycle, it may be preferable to use a saturated cyclic carbonate. In addition, as the saturated cyclic carbonate, those in which some of the hydrogen atoms are substituted with halogens may be more preferable, and those in which some of the hydrogen atoms are substituted with fluorine atoms may be even more preferable.

[0074] Examples of saturated cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), etc. Among these, from the same viewpoint as above, FEC or DFEC may be preferred in some cases, and FEC may be more preferred in other cases.

[0075] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, and bis(trifluoroethyl) carbonate.

[0076] The lower limit of the content of the unsaturated cyclic carbonate in the entire non-aqueous solvent is more than 50% by volume, preferably 60% by volume, preferably 70% by volume, and more preferably 80% by volume. On the other hand, the upper limit of the content of the unsaturated cyclic carbonate in the entire non-aqueous solvent is 100% by volume. When the content of the unsaturated cyclic carbonate is equal to or greater than the lower limit, a good coating derived from the unsaturated cyclic carbonate can be formed on the negative electrode surface. This can increase the ratio of the charge capacity at the first charge to the discharge capacity at the first discharge of the non-aqueous electrolyte storage element and the discharge capacity at the second discharge.

[0077] The content of the saturated cyclic carbonate in the total non-aqueous solvent may be 0 vol.% or more and less than 50 vol.%, 0 vol.% or more and 40 vol.% or less, 0 vol.% or more and 30 vol.% or less, or 0 vol.% or more and 20 vol.% or less.

[0078] The volume ratio of the unsaturated cyclic carbonate to the saturated cyclic carbonate (unsaturated cyclic carbonate:saturated cyclic carbonate) may be in the range of 100:0 to 51:49, or in the range of 100:0 to 60:40, or in the range of 100:0 to 70:30, or in the range of 100:0 to 80:20.

[0079] The electrolyte salt may be a lithium salt.

[0080] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts and lithium salts having a halogenated hydrocarbon group are preferred, and LiN(SO2CF3)2 is more preferred.

[0081] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0082] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of additives include oxalates such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP); imide salts such as lithium bis(fluorosulfonyl)imide (LiFSI); aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, Itaconic anhydride, cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like. These additives may be used alone or in combination of two or more.

[0083] The content of the additive contained in the nonaqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or the charge / discharge cycle performance after high-temperature storage, and to further improve safety.

[0084] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery. Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0085] [Electricity storage device] The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit. 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0086] [Method of manufacturing non-aqueous electrolyte storage element] A method for manufacturing a nonaqueous electrolyte storage element according to one embodiment of the present invention includes preparing a positive electrode containing elemental sulfur, preparing a negative electrode having a lithium alloy, and preparing a nonaqueous electrolyte containing an unsaturated cyclic carbonate, wherein the lithium alloy contains at least one of elemental aluminum, elemental indium, elemental zinc, and elemental calcium, and the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50% by volume and not more than 100% by volume.

[0087] The method for manufacturing the nonaqueous electrolyte storage element includes, as other steps, preparing an electrode body and housing the electrode body and the nonaqueous electrolyte in a container. Preparing the electrode body may be, for example, forming an electrode body by stacking or winding the positive electrode and the negative electrode via a separator. The specific configurations of the positive electrode, the negative electrode, the separator, and the nonaqueous electrolyte are as described above in the embodiment of the nonaqueous electrolyte storage element. The above configuration is applied in the process of manufacturing the nonaqueous electrolyte storage element, not in the completed nonaqueous electrolyte storage element.

[0088] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0089] [Other embodiments] The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0090] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (e.g., a lithium-sulfur battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.

[0091] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0093] [Example 1] (Preparation of positive electrode) Sulfur and porous carbon were mixed in a mass ratio of 70:30. This mixture was placed in a sealed reaction vessel, which was then placed in a sealed electric furnace. After argon flow for 1 hour, the mixture was heated to 150°C at a rate of 5°C / min and held for 5 hours, then allowed to cool to 80°C, the temperature at which sulfur solidifies, and then heated again to 300°C at a rate of 5°C / min and held for 2 hours to produce a sulfur-porous carbon composite (SPC).

[0094] A positive electrode mixture paste containing the above-mentioned sulfur-porous carbon composite (SPC), acetylene black as a conductive agent, single-walled carbon nanotubes as a conductive agent, CMC as a thickener, PAA as a binder, and SBR as a binder, using water as a dispersion medium, was applied to one side of a positive electrode substrate made of aluminum foil and dried to prepare a positive electrode.

[0095] (Preparation of negative electrode) A sheet-shaped lithium alloy (average thickness 300 μm) was laminated as a negative electrode active material layer on one side of nickel foil, which was the negative electrode substrate, and pressed. The lithium alloy was formed by dissolving metallic lithium with metallic aluminum as another metal at a content of 10 mass% (the mass ratio of lithium element and aluminum element in the lithium alloy (lithium element:aluminum element) was 90:10). In this way, a negative electrode in which a negative electrode active material layer was laminated on one side of the negative electrode substrate was produced.

[0096] (Preparation of non-aqueous electrolyte) A non-aqueous solvent containing 100% vinylene carbonate (VC) by volume was used, and LiTFSI (LiN(SO2CF3)2) was added at 1.0 mol / dm 3 The above solution was used as a non-aqueous electrolyte.

[0097] (Fabrication of non-aqueous electrolyte storage element) A single-layer electrode body was obtained using a positive electrode, a negative electrode, and a polyolefin porous resin film as a separator. The electrode body was placed in a container, and a nonaqueous electrolyte was poured into and sealed to obtain a nonaqueous electrolyte storage element of Example 1.

[0098] [Examples 2 to 8 and Comparative Examples 1 to 3] Non-aqueous electrolyte storage elements of Examples 2 to 8 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the type and content of other metals dissolved in metallic lithium in the lithium alloy of the negative electrode active material layer were as shown in Table 1. In addition, the content of unavoidable impurities in the lithium alloy of each Example and Comparative Example was 1 mass% or less. In addition, "-" in the "other metals" and "content" columns in Table 1 means that other metals dissolved in metallic lithium are substantially absent, and the negative electrode active material layer in this case is pure metallic lithium. In the above pure metallic lithium, the content of unavoidable impurities was also 1 mass% or less.

[0099] [Comparative Examples 4 to 14] Non-aqueous electrolyte storage elements of Comparative Examples 4 to 14 were obtained in the same manner as in Example 1, except that in the lithium alloy of the negative electrode active material layer, the type and content of other metals dissolved in metallic lithium were as shown in Table 1, and a non-aqueous solvent in which vinylene carbonate (VC) and fluoroethylene carbonate (FEC) were mixed in a volume ratio of 50:50 was used as the non-aqueous electrolyte.

[0100] [evaluation] Each of the obtained nonaqueous electrolyte storage elements was discharged at a constant current of 0.1C to 1V at 25°C, and the discharge capacity at this time was defined as the "discharge capacity at the first discharge". Next, constant current / constant voltage charging was performed at a current of 0.1C to 3V at 25°C until the charging time reached a total of 30 hours, and the charge capacity at this time was defined as the "charge capacity at the first charge". Furthermore, constant current discharge was performed in the same manner as above, and the discharge capacity at this time was defined as the "second discharge capacity" (discharge capacity at the second discharge). After each discharge and charge, a 10-minute pause was provided at 25°C. Discharging, charging, and pausing were all performed in a thermostatic chamber at 25°C.

[0101] Table 1 shows the discharge capacity at the first discharge, the charge capacity at the first charge, the second discharge capacity, the increase rate of the discharge capacity, and the first discharge-charge ratio. The "increase rate of the discharge capacity" is the percentage of the difference between the second discharge capacity of each nonaqueous electrolyte storage element and the second discharge capacity of the nonaqueous electrolyte storage element of Comparative Example 3 for each nonaqueous electrolyte storage element of Examples 1 to 8 and Comparative Examples 1 to 3, and is the percentage of the difference between the second discharge capacity of each nonaqueous electrolyte storage element and the second discharge capacity of the nonaqueous electrolyte storage element of Comparative Example 14 for each nonaqueous electrolyte storage element of Comparative Example 14. The "first discharge-charge ratio" is the percentage of the charge capacity at the first charge to the discharge capacity at the first discharge of each nonaqueous electrolyte storage element. In addition, the discharge capacities shown in Table 1 are all discharge capacities per unit mass of sulfur.

[0102] [Table 1]

[0103] As shown in Table 1, Examples 1 to 8, in which the lithium alloy of the negative electrode contains aluminum, indium, zinc, or calcium, and the content of VC in the nonaqueous solvent of the nonaqueous electrolyte is 100% by volume (more than 50% by volume), have a higher initial discharge-charge ratio than Comparative Example 3, in which pure metallic lithium is used in the negative electrode. In addition, Examples 1 to 8 also have a second discharge capacity that is 5% to 9% higher than Comparative Example 3.

[0104] On the other hand, in Comparative Examples 6 to 13, in which the lithium alloy of the negative electrode contains aluminum, indium, zinc, or calcium, but the content of VC in the nonaqueous solvent of the nonaqueous electrolyte is 50% by volume, the initial discharge-charge ratio was equivalent to that of Comparative Example 14, in which pure metallic lithium was used for the negative electrode. In addition, in Comparative Examples 6 to 13, the second discharge capacity was also equivalent to that of Comparative Example 14. In addition, in Comparative Examples 1, 2, 4, and 5, in which the lithium alloy of the negative electrode contains magnesium, the initial discharge-charge ratio and the second discharge capacity were all extremely small. In addition, in Comparative Examples 1 to 14, the initial discharge-charge ratio and the second discharge capacity were all smaller than those of Examples 1 to 8.

[0105] From the above, it was shown that when a lithium alloy containing a specific metal element is used for the negative electrode and the content of VC in the non-aqueous solvent of the non-aqueous electrolyte is within a certain range, the initial discharge-charge ratio and the second discharge capacity are significantly improved. [Industrial Applicability]

[0106] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0107] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode containing elemental sulfur; a negative electrode having a lithium alloy; A non-aqueous electrolyte containing an unsaturated cyclic carbonate. Equipped with The lithium alloy contains at least one of an aluminum element, an indium element, a zinc element, and a calcium element, A nonaqueous electrolyte storage element, in which the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50 vol % and 100 vol % or less.

2. 2. The nonaqueous electrolyte storage element according to claim 1, wherein the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is 70% by volume or more.

3. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the lithium alloy contains aluminum or indium, and the content of the aluminum or indium in the lithium alloy is 5% by mass or more and 20% by mass or less.

4. 3. The nonaqueous electrolyte storage element according to claim 1, wherein the lithium alloy contains zinc or calcium, and the content of the zinc or calcium element in the lithium alloy is 1% by mass or more and 10% by mass or less.

5. Providing a positive electrode containing elemental sulfur; Providing a negative electrode having a lithium alloy; Providing a non-aqueous electrolyte including an unsaturated cyclic carbonate; Equipped with The lithium alloy contains at least one of an aluminum element, an indium element, a zinc element, and a calcium element, A method for producing a nonaqueous electrolyte storage element, wherein the content of the unsaturated cyclic carbonate in the total nonaqueous solvent of the nonaqueous electrolyte is more than 50 vol % and not more than 100 vol %.

Citation Information

Patent Citations

  • Electrolyte liquid for lithium-sulfur cell, and lithium- sulfur cell using the same

    JP2002075447A